2023
DOI: 10.3389/fnins.2023.1130730
|View full text |Cite
|
Sign up to set email alerts
|

The potential of the gut microbiome for identifying Alzheimer’s disease diagnostic biomarkers and future therapies

Abstract: Being isolated from the peripheral system by the blood–brain barrier, the brain has long been considered a completely impervious tissue. However, recent findings show that the gut microbiome (GM) influences gastrointestinal and brain disorders such as Alzheimer’s disease (AD). Despite several hypotheses, such as neuroinflammation, tau hyperphosphorylation, amyloid plaques, neurofibrillary tangles, and oxidative stress, being proposed to explain the origin and progression of AD, the pathogenesis remains incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 228 publications
1
9
0
Order By: Relevance
“…The significant decrease of Faecalibacterium relative abundance has been also highlighted in individuals with subjective cognitive decline and the authors concluded that an altered gut microbiota composition may serve as a potential peripheral biomarker of AD's onset [31,32]. It is consistent with previous trials conducted in individuals suffering from NDDs revealing a lower abundance of SCFAproducing bacteria, including Prevotella, Faecalibacterium, Blautia and Roseburia compared to the gut microbiota of healthy controls [33][34][35][36][37]. In the SOD1 G93A mouse model of ALS, an increased gut permeability to toxins and a decrease of the relative abundance of the butyrate-producer Butyrivibrio fibrisolvens species were reported [38].…”
Section: Gut Microbiota and Neurodegenerative Diseases: Crosstalk And...supporting
confidence: 82%
“…The significant decrease of Faecalibacterium relative abundance has been also highlighted in individuals with subjective cognitive decline and the authors concluded that an altered gut microbiota composition may serve as a potential peripheral biomarker of AD's onset [31,32]. It is consistent with previous trials conducted in individuals suffering from NDDs revealing a lower abundance of SCFAproducing bacteria, including Prevotella, Faecalibacterium, Blautia and Roseburia compared to the gut microbiota of healthy controls [33][34][35][36][37]. In the SOD1 G93A mouse model of ALS, an increased gut permeability to toxins and a decrease of the relative abundance of the butyrate-producer Butyrivibrio fibrisolvens species were reported [38].…”
Section: Gut Microbiota and Neurodegenerative Diseases: Crosstalk And...supporting
confidence: 82%
“…The development of Alzheimer’s disease [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer’s disease have been investigated [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Numerous studies are also available regarding treatments with probiotics […”
Section: Discussionmentioning
confidence: 99%
“…This summary underscores the critical importance and urgency of using probiotics and advancing research related to cognitive aging. Ongoing studies aim to deepen our understanding of the interactions within the microbiome–gut–brain axis, particularly exploring mechanisms between the gastrointestinal tract and the nervous system [ 122 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Future research should focus on more precise analyses and explorations of the composition of gut microbiota, identifying which strains are dominantly associated with conditions such as anxiety, depression, Parkinson’s disease, and other psychiatric and cognitive disorders, including Alzheimer’s disease [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ].…”
Section: Discussionmentioning
confidence: 99%
“…Defining the specific mechanisms by which the microbiota impacts neurodegenerative processes may lead to innovative diagnostic tools and early intervention strategies [ 105 ]. Future studies should also consider the possible role of oral/nasal microbiota in diagnosing microbiota dysregulation, which could be taken into consideration as a future diagnostic tool, but more data are needed [ 106 ].…”
Section: Future Perspectivesmentioning
confidence: 99%